VMP1: a multifaceted regulator of cellular homeostasis with implications in disease pathology - Tong, Jia; Wang, Qianqian; Gao, Ziyan; Liu, Yang; Lu, Chengbiao (Frontiers in Cell and Developmental Biology, 2024)
Vacuole membrane protein 1 (VMP1) is an integral membrane protein that plays a pivotal role in cellular processes, particularly in the regulation of autophagy. Autophagy, a self-degradative mechanism, is essential for maintaining cellular homeostasis by degradation and recycling damaged organelles and proteins. VMP1 involved in the autophagic processes include the formation of autophagosomes and the subsequent fusion with lysosomes. Moreover, VMP1 modulates endoplasmic reticulum (ER) calcium levels, which is significant for various cellular functions, including protein folding and cellular signaling. Recent studies have also linked VMP1 to the cellular response against viral infections and lipid droplet (LD). Dysregulation of VMP1 has been observed in several pathological conditions, including neurodegenerative diseases such as Parkinson's disease (PD), pancreatitis, hepatitis, and tumorogenesis, underscoring its potential as a therapeutic target. This review aims to provide an overview of VMP1's multifaceted roles and its implications in disease pathology.